KEPUASAN PELANGGAN MEMEDIASI HUBUNGAN STORE IMAGE DAN EKSPEKTASI PELANGGAN TERHADAP LOYALITAS PELANGGAN - Sasi Agustin; Budiyanto Budiyanto; Mochamad Ridwan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
Store image is the combination of all customers’ attitude about a store or a company which is connected to the customers’ expectation when they choose where to shop. By designing a place to be attractive and by focusing to fulfill customers’ needs and satisfaction to shop, so that it will create a good image in the customers’ mind which is one of the elements of the store image and it will make customers’ love to shop at the first sight, therefore, a good image will be in the customers’ mind and later will create a satisfaction to that particular store. The populations in this research are customers at Carrefour Ngagel Surabaya with the minimum of 2 times to shop in the last 3 month (July, August and September 2010). Sample technique is non random sampling by using Purposive Sampling that is the sample member is determined by certain characters based on the relationship that has connected with the population characteristics. Data analyzes in this research is using Structural Equation Modeling (SEM). Based on the research, it is said that store image is influencing to the customers’ satisfaction to the customers at Carrefour Ngagel Surabaya. Customers’ expectation is influencing customers’ satisfaction at Carrefour Ngagel Surabaya. Store image doesn’t influence customers’ loyalty at Carrefour Ngagel Surabaya. Customers’ expectation is influencing customers’ loyalty at Carrefour Ngagel Surabaya. Customers’ satisfaction is influencing customers’ loyalty at Carrefour Ngagel Surabaya. Store image and customers’ expectation are significantly influence the customers’ loyalty with the customers’ satisfaction as mediation variable at Hypermart Carrefour Ngagel Surabaya.